High-Yield Formation of Substituted Tetracyanobutadienes from Reaction of Ynamides with Tetracyanoethylene - Betou, Marie; Kerisit, Nicolas; Meledje, Esme; Leroux, Yann R.; Katan, Claudine; Halet, Jean-François; Guillemin, Jean-Claude; Trolez, Yann (Chemistry : a European journal, 2014)
A high‐yielding sequence of [2+2] cycloaddition–retroelectrocyclization of ynamides with tetracyanoethylene (TCNE) is described. The reaction provided tetracyanobutadiene (TCBD) species, which were characterized by various techniques. DFT and TD‐DFT calculations were also performed to complement experimental findings. 2+2=Tetracyanobutadienes: The reaction between ynamides and tetracyanoethylene at room temperature in dichloromethane provides tetracyanobutadienes in good to quantitative yields, following a sequence of [2+2] cycloaddition–retroelectrocyclization (see scheme; EWG=electron‐withdrawing group).